(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
Nurses are expected to have the knowledge, abilities, and skills regarding nursing practice after graduating with a bachelor’s degree. However, new graduate nurses (NGNs) still lack experience in the nursing profession and cannot apply the knowledge gained in their studies to real situations. This study explored the lived experiences of NGNs in the Bone Marrow Transplant (BMT) unit. The research design used in this study was a Husserlian phenomenological method using a qualitative approach. The four steps in investigating and making meaning of lived experiences were used, which included: Epoche: This step involves bracketing or setting aside preconceived notions and assumptions about the phenomenon being studied. Reduction: This step involves identifying the essential components of the phenomenon being studied. Description: This step involves describing the phenomenon being studied richly and detailedly. Intuitive integration: This step involves synthesizing the data gathered in the previous steps to arrive at a deeper understanding of the phenomenon being studied. The study was conducted at Stanford Health Care at the BMT unit in Palo Alto, California. The participants of the study were 7 NGNs selected through purposive sampling. A researcher-made interview guide was used to gather data. The participants’ first experiences in their clinical exposure were demanding, challenging, and involved varied emotions. The study identified seven themes, namely: Expectation versus reality: NGNs often have unrealistic expectations about working as a nurse, especially in a specialized unit like BMT. They may be surprised by the work’s intensity, the patients’ complexity, and the job’s emotional demands. • Learning the ropes: NGNs must learn quickly to be effective nurses. This includes learning about the specific procedures and protocols used in the BMT unit and how to care for complex and critically ill patients. • Challenging and rewarding experiences: Working in BMT can be challenging and rewarding. NGNs may experience frustration and stress, but they may also experience great joy and satisfaction when their patients do well. • Sense of belongingness: NGNs often feel a strong sense of belongingness to the BMT team. They appreciate the support and guidance of their more experienced colleagues. • Collaboration and teamwork: Collaboration and teamwork are essential in the BMT unit. NGNs must learn to work effectively with other nurses, physicians, and healthcare professionals. • Feelings, emotions, and coping: NGNs experience a wide range of emotions on the job, including joy, sadness, frustration, and stress. They must learn how to cope with these emotions healthily. • Gratitude for being a nurse: Despite the challenges, NGNs are grateful for the opportunity to work as nurses. They feel privileged to care for patients and their families during such a difficult time. The findings of this study suggest that NGNs in the BMT unit can benefit from targeted support and education, such as: • Orientation program: A comprehensive orientation program that helps NGNs learn about the specific procedures and protocols used in the BMT unit. • Mentorship program: A mentorship program that pairs NGNs with more experienced nurses who can provide support and guidance. • Emotional support: Access to emotional support services, such as counseling or support groups, to help NGNs cope with the challenges of the job. By providing NGNs with the support and resources they need, we can help them to succeed in their careers and provide the best possible care to patients and their families.